2022
DOI: 10.3928/24748307-20220615-01
|View full text |Cite
|
Sign up to set email alerts
|

Performing an Organizational Health Literacy Assessment in a Shelter Serving People with Mental Illness

Abstract: Background: Health literacy research and practice are constantly evolving. Recent inquiry has highlighted the burdensome literacy demands faced by people with serious mental illness (SMI). Systems, organizational operations, and structures can play a role in decreasing literacy demand, thereby reducing unnecessary challenges for people with SMI. Brief Description of Activity: An organizational health literacy assessment was conducted to explore literacy demands in one m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Improving organizational VL is crucial for increasing vaccination rates, as healthcare organizations play a vital role in providing trustworthy and accessible information to the community. Specific instruments to evaluate organizational HL capacities have already been created and applied [106,107], It should be done the same for organizational VL, which should be the subject of dedicated research.…”
Section: Specific Vl Measuresmentioning
confidence: 99%
“…Improving organizational VL is crucial for increasing vaccination rates, as healthcare organizations play a vital role in providing trustworthy and accessible information to the community. Specific instruments to evaluate organizational HL capacities have already been created and applied [106,107], It should be done the same for organizational VL, which should be the subject of dedicated research.…”
Section: Specific Vl Measuresmentioning
confidence: 99%
“…Improving organizational VL is crucial for increasing vaccination rates, as healthcare organizations play a vital role in providing trustworthy and accessible information to the community. Specific instruments to evaluate organizational HL capacities have already been created and applied [100,101]. It should be performed the same way for organizational VL, which should be the subject of dedicated research.…”
Section: Specific Vl Measures and Selected Populationsmentioning
confidence: 99%
“…At least 88 percent of adults in the U.S. do not have the health literacy skills necessary to navigate the healthcare system and promote their well-being [7]. This mismatch between individual skills and healthcare system demands results in poor individual health outcomes, inefficiencies in healthcare services, and increased healthcare costs [9][10][11][12]. Poor organizational health literacy is another structural barrier that exacerbates child health inequities defined by systems barriers (e.g., racism, ableism, sexism, racial residential segregation) that largely persist across time [13].…”
Section: Introductionmentioning
confidence: 99%
“…Some research has demonstrated the importance of such assessment for organizational change to promote health equity [12,34,35]. The approach can incorporate multiple relevant systems frameworks to focus on organizational change, thereby reducing patient burden [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation